2019
DOI: 10.3390/w12010016
|View full text |Cite
|
Sign up to set email alerts
|

Gully Head-Cut Distribution Modeling Using Machine Learning Methods—A Case Study of N.W. Iran

Abstract: To more effectively prevent and manage the scourge of gully erosion in arid and semi-arid regions, we present a novel-ensemble intelligence approach-bagging-based alternating decision-tree classifier (bagging-ADTree)-and use it to model a landscape's susceptibility to gully erosion based on 18 gully-erosion conditioning factors. The model's goodness-of-fit and prediction performance are compared to three other machine learning algorithms (single alternating decision tree, rotational-forest-based alternating de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 114 publications
(166 reference statements)
0
16
0
Order By: Relevance
“…Our results are rational as the tree-based machine learning algorithms minimized bias, variance, and overfitting issues in GES modeling. This is confirmed by Arabameri et al [88], Pourghasemi et al [89], Hembram et al [87], and Gayen et al [90].…”
Section: Models Comparisonsmentioning
confidence: 55%
“…Our results are rational as the tree-based machine learning algorithms minimized bias, variance, and overfitting issues in GES modeling. This is confirmed by Arabameri et al [88], Pourghasemi et al [89], Hembram et al [87], and Gayen et al [90].…”
Section: Models Comparisonsmentioning
confidence: 55%
“…Land use underpins geomorphological and hydrological processes by affecting runoff generation, sediment dynamics, and overland flows [89]. LU/LC analysis showed that agricultural and bare landscapes, where soil is often disturbed, where surface water is often concentrated [90][91][92][93], and where the surface is often unprotected by vegetation [88], had the highest susceptibility to GE in our study region. Because GE depends on the lithology of materials at or just below the surface [5] the spatial patterns of sediment origins were evaluated.…”
Section: Discussionmentioning
confidence: 81%
“…The area under receiver operating characteristics (AUROC) curve was used to test the various models. The AUROC curve is a threshold-independent tool for the measurement of predictive performance [101][102][103][104][105][106]. The AUROC indicates the model's predictive accuracy.…”
Section: Methods For Validating the Modelsmentioning
confidence: 99%